2019
DOI: 10.1111/ibi.12741
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal patterns of population vocal activity in avian brood parasites

Abstract: Patterns of vocal activity may involve information about vocalizations themselves as well as their function. In birds, vocal activity at the individual and population level is generally closely associated with breeding cycles, reaching the peak during territorial and mating competition, and decreasing with the onset of egg incubation and chick feeding. However, little is known about patterns of vocal activity in avian brood parasites that have unusual breeding cycles without parental care. Using passive acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 42 publications
5
33
0
1
Order By: Relevance
“…Recent research has shown that acoustic signals are involved in the arms race between common cuckoos and their hosts (York and Davies, 2017;Jiang et al, 2021;Marton et al, 2021). Female common cuckoos frequently use "bubbling" calls for both interspecific and intraspecific functions during the breeding season (Deng et al, 2019b;Moskat and Hauber, 2019;Yoo et al, 2020). The starting point of our study is the question: Why are the hosts fooled by this "bubbling" call?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has shown that acoustic signals are involved in the arms race between common cuckoos and their hosts (York and Davies, 2017;Jiang et al, 2021;Marton et al, 2021). Female common cuckoos frequently use "bubbling" calls for both interspecific and intraspecific functions during the breeding season (Deng et al, 2019b;Moskat and Hauber, 2019;Yoo et al, 2020). The starting point of our study is the question: Why are the hosts fooled by this "bubbling" call?…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the "bubbling" call of female common cuckoos has been included in the long list of cuckoo tricks after the pioneering work by York and Davies (2017). This "bubbling" call type is frequently used when female common cuckoos fly or perch on branches (Deng et al, 2019b;Moskat and Hauber, 2019), and it is an ancestral character in many cuckoo species (Kim et al, 2017;Yoo et al, 2020). Thus, hosts have had sufficient opportunities to become familiar with this call and to evolve anti-parasitic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common cuckoos (Cuculus canorus) are obligate avian brood parasites that lay their eggs in the nests of other bird species, and leave the incubation and rearing of their progeny to these hosts (Payne 2005;Erritzøe et al 2012). Common cuckoos have a simple acoustic repertoire (Lei et al 2005); their most famous advertisement call ("cu-coo") is frequently emitted during the breeding season (Deng et al 2019a;Yoo et al 2020). Sometimes, this characteristic call has unique or aberrant features (Møller et al 2016), and individual cuckoos can be identified based on their call variation; for example, an individual cuckoo was tracked in Germany by its unusual calls for several years (Naumann 1901).…”
Section: Introductionmentioning
confidence: 99%